Peningkatan Kinerja Guru melalui Supervisi Akademik - Suwari, Suwari (Yayasan Sembilan Pemuda Indonesia, 2021)
The purpose of this study was to determine the effect of supervisor's academic supervision on school development and the success of supervisor's academic supervision, starting from the planning of supervision to the decision on the results of supervision at SDN 7 Muara Telang. This study uses a qualitative explanatory approach. Data collection was carried out through observation and investigation. The results showed that the principal's plan for supervision began with developing a supervision program and then maintaining contact with all teachers regarding awareness, understanding, and accountability. Furthermore, academic coaching for school principals using group and individual skills. Most school principals carry out group supervision only by training teachers at the start of the new school year. Principals generally do not supervise personal visits, notes, or individual meetings. The SDN 7 Muara Telang Principal Follow-up Program is generally oriented and implemented during teacher meetings with little interest in teachers. Principal Education Guidelines for SDN 7 Muara Telang cannot improve teacher professionalism because the coaching of school principals is unplanned, routine, and consistent.